2004
DOI: 10.1242/jeb.00825
|View full text |Cite
|
Sign up to set email alerts
|

`Futile cycle' enzymes in the flight muscles of North American bumblebees

Abstract: In the flight muscles of European bumblebees, high activities of fructose-1,6-bisphosphatase (FbPase) relative to phosphofructokinase (PFK) have suggested a thermogenic 'futile cycle' important for regional endothermy. We find generally low activities of FbPase (0.7-19.7·units·g -1 ·thorax) in North American Bombus species, with the exception of Bombus rufocinctus, where activity (43.1·units·g -1 ·thorax) is comparable with that of European congeners. These data, taken with estimates of maximal rates of heat p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 24 publications
2
17
0
Order By: Relevance
“…In this experiment, wasps were moved from a cool environment to a warmer environment; thus, some of the rapid warming observed may have been due to the inspiration of warmer ambient air, although this cannot explain those wasps that had body region temperatures above ambient. Our results raise the question of whether some or all of this temperature increase could be due to a futile cycle as has been observed in bumblebees (Surholt et al, 1991;Staples et al, 2004). While the futile cycle does not appear to be a large part of warming in bumblebees (Staples et al, 2004), the weak temperature elevation observed at low temperatures in Polistes could potentially be caused by a futile cycle.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…In this experiment, wasps were moved from a cool environment to a warmer environment; thus, some of the rapid warming observed may have been due to the inspiration of warmer ambient air, although this cannot explain those wasps that had body region temperatures above ambient. Our results raise the question of whether some or all of this temperature increase could be due to a futile cycle as has been observed in bumblebees (Surholt et al, 1991;Staples et al, 2004). While the futile cycle does not appear to be a large part of warming in bumblebees (Staples et al, 2004), the weak temperature elevation observed at low temperatures in Polistes could potentially be caused by a futile cycle.…”
Section: Discussionsupporting
confidence: 50%
“…Our results raise the question of whether some or all of this temperature increase could be due to a futile cycle as has been observed in bumblebees (Surholt et al, 1991;Staples et al, 2004). While the futile cycle does not appear to be a large part of warming in bumblebees (Staples et al, 2004), the weak temperature elevation observed at low temperatures in Polistes could potentially be caused by a futile cycle. Further testing is required to address this possibility.…”
Section: Discussionsupporting
confidence: 50%
“…The responsible mechanism for the enhanced respiration is as yet unknown, but increased muscular activity is discussed in this context (Plath and Boersma 2001). Another potential source of increased respiration rates is feeding-induced thermogenesis (Staples et al 2004;Zanotto et al 1997). Heat could be produced by fuelling two opposing enzymatic reactions at the same time, which is costly in terms of energy, but no net changes in either the concentration of substrate or product occurs (Newsholme and Crabtree 1976;Newsholme et al 1972).…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to vertebrates, FBPase activity in insect muscle tissues is higher than that in the fat body Kasprzyk 1993). We have detected and localized, for the first time, FBPase activity in insect ovarian tissue; the highest FBPase activity has been observed in the homogenate of I. cimicoides (Heteroptera), although its value is approximately 25 times lower than that reported for the flight muscle of Lethocerus cordofanus (Hemiptera), 10-300 times lower than that in the thoracic flight muscle of north American Bombus species (Staples et al 2004), 1,000 times lower than that reported for the flight muscle of Bombyx mori (Lepidoptera) Newsholme et al 1972;Greive and Surholt 1990), and 10 times lower that compared with overwintering larvae of the Shonai ecotype of the rice stem borer, Chilo suppressalis (Lepidoptera) (Li et al 2002a). FBPase activity in the homogenates of insect ovarian tissue is half that reported for FBPase in the fat body of Periplaneta americana (Blattaria) and Tenebrio molitor (Coleoptera) (Kasprzyk 1998).…”
Section: Discussionmentioning
confidence: 69%